Слаботочные диоды Ганна на основе арсенида галлия для КВЧ-аппаратов - Yatsunenko, A. G.; Kovtonyk, V. M.; Ivanov, V. N.; Nikolaenko, Yu. E. (PE "Politekhperiodika", Book and Journal Publishers, 2005)
A hardware implementation of multichannel domestic millimeter-wave therapy devices based on Gunn diodes operating in the frequency ranges of 42–53 GHz and 56–65 GHz with operating currents below 120 mA has been carried out. New technologies for forming a cathode contact with limited injection of majority carriers from AuGe–TiB2–Au allow the fabrication of diodes with a conversion efficiency of DC voltage into microwave oscillations exceeding 2% and a maximum output power up to 10 mW. This makes it possible to significantly improve the performance characteristics of millimeter-wave equipment and expand its functional capabilities.